Spectral-detector based x-ray absorptiometry (SDXA): in-vivo bone mineral density measurements in patients with and without osteoporotic fractures. (24th August 2020) - Laugerette, Alexis; Baum, Thomas; Gersing, Alexandra S; Schwaiger, Benedikt J; Brown, Kevin; Frerking, Lena C; Shapira, Nadav; Pfeiffer, Daniela; Rummeny, Ernst J; Proksa, Roland; Pfeiffer, Franz; Noël, Peter B
Abstract: Objectives : To study whether a dual-layer spectral CT scout scan-based areal BMD estimation method, called Spectral-detector based x-ray absorptiometry (SDXA), can differentiate patients with versus without osteoporotic fractures. Methods: The ability of the method to differentiate patients with osteoporosis was evaluated by assessing the areal BMD at the spine (L1 to L4) in a group of 19 patients presenting at least one fracture and comparing these results to the areal BMD of age- and gender-matched controls (57 patients). Finally, the reproducibility of SDXA was evaluated in-vivo through the calculation of coefficients of variation (CV), using three repeated analyses performed on each patient. Results : The average areal BMD of patients presenting fractures, measured with the scout scan-based method (0.86 ± 0.17 g cm −2 ), was found to be significantly lower than the average BMD of the control group (1.00 ± 0.17 g cm −2, p = 0.043). The reproducibility of the method in-vivo was found to be reasonable, with CVs ranging between 3.1 and 6.9%. Conclusions : The results illustrate that the SDXA method for DXA-equivalent areal BMD estimation -delivers the ability to distinguish patients presenting osteoporotic fractures. Considering the total number of CT examinations worldwide, SDXA could develop to be a useful tool for truly opportunistic osteoporosis screening for a future clinical day-to-day routine.